Impact of Control Availability on Perceived Comfort. (November 2015) - Guo, Hongshan; Meggers, Forrest
Abstract: Open plan offices are known for improving the interaction among occupants while risking their comfort. Traditionally considered to be caused by deprivation of privacy and safety, the discomfort is also recently attributed to occupants' lost of control availability. According to some studies, improving perceived control could improve perceived comfort. However, few studies investigated the correlation with variations of control availability. An investigation is therefore presented in this paper that examines the impact of different levels of control availabilities' on perceived thermal comfort, for which a potential gap of thermal neutrality was identified as the availability of control increased.